2016
DOI: 10.1631/jzus.b1500120
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physiological properties and kinetics of citric acid accumulation via carbon ion irradiation mutagenesis of Aspergillus niger

Abstract: Abstract:The objective of this work was to produce citric acid from corn starch using a newly isolated mutant of Aspergillus niger, and to analyze the relationship between changes in the physiological properties of A. niger induced by carbon ion irradiation and citric acid accumulation. Our results showed that the physiological characteristics of conidia in A. niger were closely related to citric acid accumulation and that lower growth rate and viability of conidia may be beneficial to citric acid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Heavy ion mutagenesis is a powerful and high-efficient tool that has been readily applied in mutagenesis of bacteria, fungi and microalgae [ 29 ]. Compared with low-LET (about 0.2-5KeV/μ) mutation induction techniques (X-rays or ɣ-rays)[ 30 , 31 ], high-LET heavy ion beams can cause double-strand DNA break [ 32 ] owing to denser ionization along their trajectories, which induced different types of DNA damage, such as, translocations, inversions, insertion, and DNA deletions, which would be valuable for obtaining diverse phenotypic microbial mutants for functional genes research.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy ion mutagenesis is a powerful and high-efficient tool that has been readily applied in mutagenesis of bacteria, fungi and microalgae [ 29 ]. Compared with low-LET (about 0.2-5KeV/μ) mutation induction techniques (X-rays or ɣ-rays)[ 30 , 31 ], high-LET heavy ion beams can cause double-strand DNA break [ 32 ] owing to denser ionization along their trajectories, which induced different types of DNA damage, such as, translocations, inversions, insertion, and DNA deletions, which would be valuable for obtaining diverse phenotypic microbial mutants for functional genes research.…”
Section: Discussionmentioning
confidence: 99%
“…É conhecido que a fonte de carbono e de fosfato mais adequada para a produção do ácido cítrico, são a sacarose e o fosfato de potássio monobásico, respectivamente (FOSTER, 1949;GREWAL et al, 1995;RODRIGUES, 2006;PASTORE et al, 2011). O fungo A. niger é amplamente descrito na literatura para a produção de ácido cítrico (RODRIGUES, 2006;AUTA et al, 2014;HU et al, 2014;HU et al, 2016). Porém,…”
Section: O Gênero Aspergillus E O Acúmulo De áCido Cítricounclassified
“…10; Based on these results, Chen et al (2010) screened high-producing-avermetin-Bla strain ZJAV-Y203 from the original strain Streptomyces avermitilis (ZJAV-A1) irradiated by carbon ion beam with different doses, the Bla component increased by 51.43%. In recent years, a high-yielding citric acid mutant, HW2, was obtained from Aspergillus niger induced by carbon ion irradiation which can accumulate 118.9 g/L citric acid with a residual total sugar concentration of only 14.4 g/L in a 10-L bioreactor (Hu et al, 2016). Zhou et al (2016) investigated the utility of two rounds of heavy ion beam irradiation to create Clostridium tyrobutyricum mutants with improved bioproduction capability under acidic conditions and revealed that carbon ions effectively induced the expression of key enzymes in glycolysis, product formation, energy and redox metabolism and the cellular response to butyric acid production.…”
Section: Improvmentioning
confidence: 99%